Review of the genus Trichiotes Casey (Coleoptera: Tenebrionidae: Pimeliinae: Edrotini), with the description of a new species and a preliminary checklist of the Tenebrionidae from Cuatrociénegas, Mexico - Wirth, Christopher C.; Smith, Aaron D. (Zootaxa, 2017)
The rarely collected, previously monotypic, darkling beetle genus Trichiotes is reviewed, including new state and country records for T. seriatus Casey, 1907 and a new species, Trichiotes lightfooti Wirth & Smith, n. sp., is described from the Cuatrociénegas Protected Area in Coahuila, Mexico. Differences in stridulatory structures between the species are discussed and the occurrence of a waxy, extracuticular pruinescence is reported for Trichiotes. A species key to the genus is provided and a checklist of the known Tenebrionidae from the Cuatrociénegas region is presented.